Oxidative stress and p53 mutations in the carcinogenesis of iron overload-associated hepatocellular carcinoma - Marrogi, Aizen J.; Bartsch, Helmut (Journal of the National Cancer Institute, 2001)
Increased NOS-2 expression has been associated with several malignancies (19-22) and preneoplastic chronic inflammatory conditions (20,23-26). The overexpression of NOS-2 and NO in the non-neoplastic hepatic regenerative nodules—that are both preneoplastic and associated with increased risk of HCC—as presented here indicates a possible role in hepatic carcinogenesis. Although the frequency of NOS-2 overexpression in the non-neoplastic hemochromatosis tissues adjacent to the tumors is higher in our study than reported previously (57% versus 28%), the disease grade is different, because all of our samples were cirrhotic compared with 33% in our previous work (11). NO generated by NOS-2 has been reported to induce mutations in vitro and in animal models (27,28), and DNA damage by several mechanisms, such as nitrosamide deamination or induction of lipid peroxidation (28,29), as well as undermine cellular DNA repair processes performed by DNA glycosylase (30). In addition, ionic iron has been shown to modulate NO-mediated cell death and apoptosis (31). We have reported higher NOS-2 enzymatic activity in colonic adenomas than in colonic carcinomas (19). Furthermore, high levels of NOS-2 are associated with p53 mutations in colorectal neoplasms, particularly those with G : C to A : T transitions at CpG dinucleotides by a mechanism of NO-increased deamination of 5-methylcytosine (19,32). However, the p53 mutation spectrum in HCC associated with hemochromatosis reported here and elsewhere (15) is more consistent with some other unknown endogenous mutagenic mechanism that is mediated by lipid peroxidation, based on the types of mutations detected. The increase in etheno -dG and -dA DNA adducts, caused by lipid peroxidation in liver tissues from hemochromatosis patients (33,34), and the p53 mutational load (11) in liver tissue from individuals with hemochromatosis are both consistent with the hypothesis of generation of oxyradicals as an underlying mechanism of cancer in heavy metal overload diseases (16).
Gesehen am 12.01.2021